2015
DOI: 10.1016/j.cmi.2015.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Impact of urinary tract infections on short-term kidney graft outcome

Abstract: Urinary tract infections (UTIs) are frequent after renal transplantation, but their impact on short-term graft outcome is not well established. All kidney transplants performed between July 2003 and December 2010 were investigated to evaluate the impact of UTI on graft function at 1 year after transplantation. Of 867 patients who received a kidney transplant, 184 (21%) developed at least one episode of UTI, at a median of 18 days after transplantation. The prevalence of acute graft pyelonephritis (AGP) was 15%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
6
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 30 publications
2
36
6
5
Order By: Relevance
“…We identified antibiotic use for UTI as an independent risk factor for CDI (AOR = 4.17, 95% CI = 1.12‐15.54, P = .034). The UTI indication is not surprising as it is the most common infection post–renal transplant . Unpublished data at our institution over a 5‐year time frame shows that asymptomatic bacteriuria was treated 75% of the time with antibiotics.…”
Section: Discussionmentioning
confidence: 93%
“…We identified antibiotic use for UTI as an independent risk factor for CDI (AOR = 4.17, 95% CI = 1.12‐15.54, P = .034). The UTI indication is not surprising as it is the most common infection post–renal transplant . Unpublished data at our institution over a 5‐year time frame shows that asymptomatic bacteriuria was treated 75% of the time with antibiotics.…”
Section: Discussionmentioning
confidence: 93%
“…Several hypotheses may explain the negative impact of infection on graft function, but it is most likely that bacterial infection activates the immune system, thereby inducing acute or chronic rejection and negatively affecting graft function. In kidney recipients, for example, acute graft pyelonephritis has been associated with graft dysfunction and loss . Moreover, when Kamath et al reported that 41% and 28% of patients experienced acute rejection episodes before and after an episode of acute graft pyelonephritis, respectively, they concluded that the process of infection and immune activation can be bidirectional.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies evaluated the incidence of ASB during the first month after KT, finding a pooled incidence of 22% for the first month after KT (Figure S3) with almost no heterogeneity . On the other hand, 10 studies reported data regarding the incidence of ASB during the first year after KT, finding an overall value of 32% (Figure S4) with significantly high heterogeneity (99%) …”
Section: Resultsmentioning
confidence: 99%
“…Five studies published in the literature have examined the risk of AGR in KT patients with ASB. 4,16,17,20,23 In the meta-analysis, there was no difference between the presence of at least one ASB episode during the first year after KT (n = 551) compared to no ASB episodes during this period (n = 934) regarding the risk for AGR F I G U R E 1 Flowchart diagram of studies selection occurrence (OR 1.09; 95% CI 0.53-2.25), result with a low heterogeneity (I 2 = 48%) ( Figure 2). 16,17,20…”
Section: Asymptomatic Bacteriuria and The Risk Of Agrmentioning
confidence: 99%